Pembinaan Prestasi Olahraga Atletik di Kabupaten Demak - Adi Indra Purnama; Hermawan Pamot Raharjo (Universitas Negeri Semarang, 2023)
This study aims to determine the development of athletic sports achievement in Demak Regency. The method used is a combination of quantitative and qualitative with a population of 12 athletes and 10 coaches. The sample used for all athletes and coaches in Demak Regency found 22 people. The test instrument used observation, questionnaires and interviews. The analysis technique uses the score percentage formula and the descriptive category table percentage from Anas Sudjiono 2012. The results show the moderate category with a percentage of 31.81%: (1) coaching athletic sports achievement in Demak district based on the athlete's point of view is in the good category with a percentage of 50% . (2) the development of athletic sports achievements in Demak Regency based on the administrator's/coach's point of view is in the moderate category with a percentage of 50%. Based on the results of data analysis, description of research results, and discussion, it can be concluded that the development of athletic sports achievements in Demak Regency from the point of view of coaches/managers and athletes still has obstacles in facilities and infrastructure that are still incomplete and athletic sports development in Demak Regency is still in progress.